The Concentrations and Distributions of Heavy Metals Pb, Cu and Zn in the Sea Water and Sediment in Estuary Area of Dumai, Riau Province. - Nurhuda, Ahmad; Amin, Bintal; ', Mubarak (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research of heavy metal (Pb, Cu, Zn) has been conducted in June 2015in the estuary area of Dumai, Riau Province. The samples of water and sedimentwere taken in difference area, consisting of 15 stations by purposive samplingmethod. The analysis showed heavy metal contents were as followes Pb 0.051 –0.061 mg/l, Cu 0.038 – 0.047 mg/l, and Zn 0.182 – 0.243 mg/l respectively. Theheavy metal contents in water has exceeded the quality standard ofKep.MENLH/51/2004 on sea water quality standard for marine organism. On theother hand, the sediment analysis showed heavy metal contents were Pb 2.700 –3.500 μg/g, Cu 2.522 – 6.97 μg/g and Zn 15.977 – 18.059 μg/g. According to thisresearch it was concluded that the estuary area of Dumai has been contaminated.Key words : Heavy metal, seawater, sediment, estuary area of Dumai.